Penutupan Ruang Bekas Pencabutan Premolar Satu - Evie D. D. Yashadhana; Maria Purbiati (Faculty of Dentistry, Universitas Indonesia, 2015)
The aim of the present study was to investigate the amount of protraction of the anchor teeth (M1), as  a result of the retraction of the upper anterior dentition in protrusion cases with extraction of bot upper first premolars, using only upper first permanent molars as anchorage. This condition is surprisingly paid little attention. The data were obtained from pre and post treatment upper dental casts of Class I and Class II malocclusion with protrusion and slight crowding. After ecctraction of two upper first premolars, all patients were treated with fixed appliances. Measurement was gathered by using Coordinate Measuring Machine. The findings from statistical data analysis showed that the closing of the first Premolar extraction space was caused not only by the retraction of the anterior teeth, but also by the protraction of the upper first Molars as big as 40.4%. Compared to both right and left side of the arch, the probabiity of the posterior tooth protraction was even. It was not an anchorage loss investigation but the result indeed would take clinician's more attention to control the anchorage.